1996
DOI: 10.1007/bf00417899
|View full text |Cite
|
Sign up to set email alerts
|

Prandial aspiration and pneumonia in an elderly population followed over 3 years

Abstract: The purpose of our study was to prospectively determine pneumonia frequency and correlate it with prandial liquid aspiration and feeding status in frail elderly nursing home residents. Initially, 152 patients had video swallowing examinations (81 oropharyngeal dysphagia, 19 thoracic dysphagia, 52 without dysphagia). Those diagnosed with oropharyngeal impairment were subsequently managed with swallowing therapy or artificial feeding modalities. Patients were followed for 3 years (unless they expired earlier) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 28 publications
1
43
0
3
Order By: Relevance
“…Societal factors, anxiety, food palatability, and the degree of hunger or satiety modify eating and swallowing rate in normal subjects [14][15][16][17][18]. Psychosocial factors influence the presence and timing of aspiration of elderly nursing home patients [19]. Conversely, many oral sensations, such as food textures, taste, temperature, and volume, may alter pre-oral feeding behavior.…”
Section: Pre-oral (Anticipatory) Stage: Interstage Relationshipsmentioning
confidence: 99%
“…Societal factors, anxiety, food palatability, and the degree of hunger or satiety modify eating and swallowing rate in normal subjects [14][15][16][17][18]. Psychosocial factors influence the presence and timing of aspiration of elderly nursing home patients [19]. Conversely, many oral sensations, such as food textures, taste, temperature, and volume, may alter pre-oral feeding behavior.…”
Section: Pre-oral (Anticipatory) Stage: Interstage Relationshipsmentioning
confidence: 99%
“…Since dysphagia predisposes to aspiration, the relationship between dysphagia and aspiration pneumonia might appear obvious, but evidence for this has not always been found [31][32][33]. In fact, several studies of tube-fed patients who are taking no food or liquid by mouth have shown that tube feeding is associated with a higher rate of pneumonia than in patients who are eating [19,23,28,30,31,33,34]. A large body of literature has focused on the association between gastroesophageal reflux and aspiration [18,[35][36][37][38][39][40][41][42].…”
mentioning
confidence: 99%
“…The reports of pneumonia were obtained from patient reflections, but it appears highly likely that the patients had suffered no pneumonia serious enough to require hospitalization. Since swallowing dysfunction causes aspiration, a relationship between swallowing dysfunction and aspiration pneumonia would appear highly likely, but there is no consistent evidence of this [20][21][22] not recover during the period until the follow up reported here. However, the results of the present study were determined by the retrospective study design, therefore to assess the post-surgical swallowing function after a further five years with the sample of the present study would be relevant to support the results of the present study.…”
Section: Discussionmentioning
confidence: 60%